AB0318 Clinical and serologic characteristics of a cohort of ecuadorian men with rheumatoid arthritis. (15th June 2017) - Maldonado, G; Ferro, C; Guerrero, R; Paredes, C; Rios, C
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory and disabling disease whose expression and clinical course is influenced by gender. In developed countries the prevalence of RA is 0.5–1%, with a ratio 3:1 female:male. Comparative gender studies have shown that women have greater functional disability, disease activity and pain than men1. Objectives: The purpose of this study is to describe and compare the clinical and serological characteristics of a cohort of men with RA. Methods: A cross-sectional study was conducted in patients with established diagnosis of RA (American College of Rheumatology criteria 1988) from the Luis Vernaza Hospital and a private rheumatology center (CERER). The data included clinical manifestations, demographic data, comorbidities, habits, treatment, activity index DAS28-CRP, HAQ-DI disability index and the PHQ-9 questionnaire. The statistical program SPSS V. 22 was used to analyze the data and calculate frequencies, percentages, means, ranges, Spearman correlation and ANOVA coefficient. Statistical significance used was 0.05, with a 95% reliability. Results: A cohort of 50 men was compared with a control group of 50 women. Most men worked while women stayed at home (72% and 66%, respectively, p=0.000). Tobacco and alcohol were more common in men (34% vs 8% p=0.001 and 38% vs. 0% p=0.000 respectively). The delay in the first visit to the specialist was shorter in men than in women (24 vs 32 months) and they had a longer follow-up (55 vs 41 months). In clinical manifestations, women had greater fatigue (60% vs 30% p=0.003), weight loss (44% vs 20% p=0.010), loss of appetite (54% vs 12% p=0.000) and depression (60% vs 22% p=0.000). There was no significant difference in comorbidities and treatment between the groups. Men had lower disease activity: VSG (23 vs 47 p=0.046), DAS 28 (2.5 vs 3.4 p=0.011), HAQ DI (0.37 vs 1.12 p=0.000), functional disability (12% vs 36% p=0.005), severe disability (2% vs 22% p=0.002), painful joints (2 vs 8 p=0.000), swollen joints (2 vs 6 p=0.000) and VAS of doctor (2 vs 3 p=0.047). Conclusions: This is the first cohort study of men with RA in Ecuador. As shown in other international studies2–3, our results confirm that men have a less aggressive disease. References: Lesuis N, Befrits R, Nyberg F, van Vollenhoven RF. Gender and the treatment of immune-mediated chronic inflammatory diseases: rheumatoid arthritis, inflammatory bowel disease and psoriasis: an observational study. BMC Med. BioMed Central Ltd;2012;10(1):82. Sokka T, Toloza S, Cutolo M, Kautuainen H, Makinen H. Women, men, and rheumatoid arthritis: analyses of disease activity, disease characteristics, and treatments in the QUEST-RA Study. Arthritis Res Ther. 2009;11(1):1–12. Hallert E, Thyberg I, Hass U, Skargren E, Skogh T. Comparison between women and men with recent onset rheumatoid arthritis of disease activity and functional ability over two years (the TIRA project). Ann Rheum Dis. 2003;62(7):667–70. Disclosure of Interest: None declared